Computação Autonômica Aplicada à Criminalística Computacional - Nogueira, José Helano Matos; Celestino Júnior, Joaquim (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2008: Companion Proceedings of the 8th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2008.20907, 2008)
This article does not have an abstract.